Penyuluhan Pentingnya Pembukuan Umkm Sederhana Dan Tahapan Penyusunan Studi Kelayakan Usaha - Bakri Katti, Siti Wardani; Mutmainah, Mutmainah (JURNAL DAYA-MAS, 2020)
Abstract— MSMEs are one of the importance elements in supporting the national economy. The sustainability of MSMEs must be maintained and developed. For this reason, it is necessary business feasibility studies. Furthermore, more important for MSME entrepreneurs to know is the importance of making simple accountancy. So, making decisions can more easy, comprehensive, and focus. The use of financial report or simple accountancy make easy entrepreneurs of MSME and others partner for analyze that MSMEs performance. This activity use lecture method and making simple accountancy practice directly. The participant of this activity are society of Dempelan village, both entrepreneurs and nonentrepreneurs. This activity had attended enthusiastically society of Dempelan village. It was caused that society got new knowledge about simple accountancy and making business feasibility study. Business feasibility study are very important to thie entrepreneurs, so they know their business position in market and future prospects. Keywords—: Accountancy; MSME; business feasibility study.